Making the miscellany : poetry, print, and the history of the book in early modern England - Heffernan, Megan (University of Pennsylvania Press, 2021)
In Making the Miscellany Megan Heffernan examines the poetic design of early modern printed books and explores how volumes of compiled poems, which have always existed in practice, responded to media change in sixteenth- and seventeenth-century England. Heffernan's focus is not only the material organization of printed poetry, but also how those conventions and innovations of arrangement contributed to vernacular poetic craft, the consolidation of ideals of individual authorship, and centuries of literary history. The arrangement of printed compilations contains a largely unstudied and undertheorized archive of poetic form, Heffernan argues. In an evolving system of textual transmission, compilers were experimenting with how to contain individual poems within larger volumes. By paying attention to how they navigated and shaped the exchanges between poems and their organization, she reveals how we can witness the basic power of imaginative writing over the material text. Making the Miscellany is also a study of how this history of textual design has been differently told by the distinct disciplines of bibliography or book history and literary studies, each of which has handled--and obscured--the formal qualities of early modern poetry compilations and the practices that produced them. Revisiting these editorial and critical approaches, this book recovers a moment when compilers, poets, and readers were alert to a poetics of organization that exceeded the limits of the individual poem.--